PERAN PEREMPUAN ISLAM DALAM PEMBANGUNAN DESA DI KABUPATEN BONE BOLANGO - Hendra Yasin; Jurisman Kadji (Farabi, 2022)
Abstract: Seeing the extent to which the role and constraints of Islamic women in village development in Bone Bolango district, Gorontalo Province is interesting to observe. At least because the context of bone bolango is so strong in its customs and Islam that often differentiates women and men. Although in Islam the role of women is not a problem. However, in the context of Gorontalo custom, more specifically in Bone Bolango, there is a place that has a traditional nuance, which women cannot enter. However, there is something that can be said to be an anomaly, namely the presence of women in filling the sub-district office. There are even female deputy district heads who were born from a direct election process. This type of research is Mixed Method Research (MMR) with Explanatory type. The research location is in Bone Bolango district. Using a structuration theory framework approach which includes structure and agency the researcher concludes several things namely women have a big role in village development in Bone Bolango Regency. Structurally, women receive support including significance (stock of knowledge), legitimacy (rules that favor women) and domination (authority/power that is pro-women). In terms of agency/women themselves have the capacity and capability, especially in terms of networking. Even so, it cannot be denied that culture contributes to hindering the role of women. Keywords: Role, Islamic Women, Structuration